Different and Often Opposing Forces Drive the Encapsulation and Multiple Exterior Binding of Charged Guests to a M4L6 Supramolecular Vessel in Water. Issue 66 (8th November 2017) - Sgarlata, Carmelo; Mugridge, Jeffrey S.; Pluth, Michael D.; Zito, Valeria; Arena, Giuseppe; Raymond, Kenneth N.
Abstract: The supramolecular assembly [Ga4 L6 ] 12− acts as a nanoscale flask to mediate the reactivity of encapsulated reactive guests and also functions as a catalyst to carry out enzyme‐like chemical transformations. The guest binding to the interior cavity and exterior of this host is difficult to untangle because multiple equilibria occur in solution, and only when refining simultaneously data obtained from different techniques, such as NMR, UV/Vis, and calorimetry, can the accurate solution thermodynamics of these host–guest systems be determined. This study reports the driving forces for the inclusion and stepwise exterior guest binding of different aliphatic quaternary ammonium guests to the [Ga4 L6 ] 12− assembly. Encapsulation into the host cavity was found to be an entropy‐driven process, whereas exterior ion association is driven either by enthalpically favorable attractive forces or by the entropy gain due to desolvation, depending on guest size and character. The analysis of the energetics of reaction may help predicting and understanding the intimate role and contribution of the transition state in those rate‐accelerated reactions involving this supramolecular assembly as an enzyme‐like molecular flask. Abstract : The driving forces for the encapsulation and exterior binding of quaternary ammonium guests to the [Ga4 L6 ] 12− assembly in water are discussed. Encapsulation into the host cavity is always an entropy‐driven process, whereas exterior ion‐association strongly depends on guest size and character. The energetics of guest binding may help understanding the role of the transition state in rate accelerated reactions promoted by this molecular flask (see scheme).